STATUS NUTRSI PASIEN KANKER YANG MENJALANI KEMOTERAPI DI RSUD Prof Dr W. Z JOHANNES KUPANG - Fransiskus S. Onggang; Bringiwatty Batbual; Aben B.Y. H. Romana; Agustina Ina; Jane Leo Mangi; Gadur Blasius; Maria Sambriong; Dominggos Gonsalves; Mariana Oni Betan; Oklan BT Liunokas (Journal of Innovation Research and Knowledge, 2025)
Cancer is one of the diseases with the highest mortality rate in the world. Every year the number of cancer patients in the world increases to 6.25 million people. WHO estimates that 500,000 new cases of breast cancer are diagnosed with a death toll of approximately 3,750 deaths per year. Objective: Education with booklet media can increase patient knowledge about good nutrition during chemotherapy. This study aims to analyze the effect of booklets on the level of knowledge of cancer patients at RSUD Prof. Dr. W. Z. Johannes Kupang Hospital. Methods: This study used a pre experiment one group pre-post test design with 38 cancer patient respondents. The variables analyzed included the level of knowledge before and after the booklet intervention. Data were analyzed using the Wilchoxon statistical test and cross tab. Results: There is an effect of education with booklet media, where it is obtained asymp. Sig (2-tailed) is 0.000 <0.05. Conclusion: There is an effect of education through booklet media about nutrition on the level of knowledge in patients undergoing chemotherapy at Prof. Dr. W. Z. Hospital Kupang. Johannes Kupang Hospital. Suggestion: It is hoped that this study can provide information and input to cancer patients undergoing chemotherapy at Prof. Dr. W. Z. Johannes Kupang, about nutritional knowledge so that they can practice it and the hospital can explain more about nutrition to all patients at RSUD Prof. Dr. W. Z. Johannes Kupang Hospital